2022
DOI: 10.1021/acs.est.2c02117
|View full text |Cite
|
Sign up to set email alerts
|

Application of the IoT in the Food Supply Chain─From the Perspective of Carbon Mitigation

Abstract: With the rising demands on supply chain transparency and food security, the rapid outspread of the Internet of Things (IoT) to improve logistical efficiency, and the rising penetration of sensor technology into daily life, the extensive integration of the IoT in the food sector is well anticipated. A perspective on potential life cycle trade-offs in regard to the type of integration is necessary. We conduct life cycle assessment (LCA) integrated with shelf life−food loss (SL−FL) models, showing an overall 5-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Following this, Table 3 is presented, displaying the Research Approach, which allowed for the organization of all the identified research in this study. Monitoring and Supervising (Bhatia & Albarrak, 2023); (R. Gupta & Shankar, 2023); (Rajput et al, 2023); (Khan et al, 2022); (Yakubu et al, 2022); (Lee et al, 2021); (Scuderi et al, 2022); (Bansal et al, 2022); (Luo et al, 2022); (Kazancoglu et al, 2022); (Abdulhussein et al, 2020); (Patra et al, 2021); (AlJemy et al, 2019);…”
Section: Development and Resultsmentioning
confidence: 99%
“…Following this, Table 3 is presented, displaying the Research Approach, which allowed for the organization of all the identified research in this study. Monitoring and Supervising (Bhatia & Albarrak, 2023); (R. Gupta & Shankar, 2023); (Rajput et al, 2023); (Khan et al, 2022); (Yakubu et al, 2022); (Lee et al, 2021); (Scuderi et al, 2022); (Bansal et al, 2022); (Luo et al, 2022); (Kazancoglu et al, 2022); (Abdulhussein et al, 2020); (Patra et al, 2021); (AlJemy et al, 2019);…”
Section: Development and Resultsmentioning
confidence: 99%
“…C i , j stands for the supply-embodied GHG emissions of the food commodity j in country i (Table ), , which refers to all GHG emissions of the food commodity being derived from planting and all activities associated with logistics in the supply chain, including 9 postfarming stages from harvest to the consumer. CFC i , j stands for the GHG emissions of consumed food commodity j in country/region i at the consumer stage subjected to logistic activities from harvest to retail (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…There is a need for decentralized solutions such as blockchain due to the single points of failure, product irregularities, quality compromises, and loss of data present in conventional food supply chains. Adoption of blockchain in the food supply chain, especially when combined with other technologies such as IoT, enables data interoperability, cost reduction, transparency, auditability, integrity and authenticity ( Casino et al, 2021 ; Luo et al, 2022 ). To protect vulnerable populations, blockchain solutions that go beyond food traceability to maintaining the nutritional values of dairy products, and identification of their adulteration and contamination have been proposed ( Khanna et al, 2022 ).…”
Section: Dairy 40 Enabling Technologiesmentioning
confidence: 99%